2018
DOI: 10.1029/2018jd028726
|View full text |Cite
|
Sign up to set email alerts
|

Cirrus Horizontal Heterogeneity and 3‐D Radiative Effects on Cloud Optical Property Retrievals From MODIS Near to Thermal Infrared Channels as a Function of Spatial Resolution

Abstract: To retrieve cloud optical properties, current satellite operational imager algorithms simplify the forward radiative transfer problem by assuming that cloudy pixels are horizontally homogeneous and radiatively independent. This study investigates the effects of cirrus horizontal heterogeneity and 3-D radiative effects on cloud optical thickness (COT) and ice crystal effective radius (CER) retrievals obtained using simulated nadir near-infrared/shortwave-infrared (NIR/SWIR) reflectances at 0.86 and 2.13 μm and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…IIR De might be larger than MODIS 3.7 and in better agreement with MODIS 2.1 for opaque clouds at Tr < 220 K because the IIR weighting function is deeper into the cloud than at 3.7 µm, which is agreement with simulations by Zhang et al (2010). In conclusion, distinct sensitivity to 490 possible cloud vertical and horizontal (Fauchez et al, 2018) inhomogeneity likely contributes to the observed differences.…”
Section: Comparisons With Modissupporting
confidence: 69%
“…IIR De might be larger than MODIS 3.7 and in better agreement with MODIS 2.1 for opaque clouds at Tr < 220 K because the IIR weighting function is deeper into the cloud than at 3.7 µm, which is agreement with simulations by Zhang et al (2010). In conclusion, distinct sensitivity to 490 possible cloud vertical and horizontal (Fauchez et al, 2018) inhomogeneity likely contributes to the observed differences.…”
Section: Comparisons With Modissupporting
confidence: 69%
“…Here, average values are reported of at least 1,000 POLDER pixels, and most random errors can be assumed to average out. Local biases because of, for example, subpixel inhomogeneity (Fauchez et al, 2018; Zhang et al, 2016 ) cannot be ruled out. If we take as a measure for inhomogeneity the standard deviation of MODIS cloud optical thicknesses within a POLDER footprint, as provided in the combined POLDER‐MODIS data set, relative to the corresponding mean optical thickness, we find that inhomogeneity increases with mean optical thickness but do not find any other apparent correlation with inhomogeneity and retrieved ice properties.…”
Section: Methods and Datamentioning
confidence: 99%
“…In the process of retrieving cloud properties, each cloudy pixel is considered to be independent of its neighboring pixels [64]. Therefore, differences among neighboring MODIS pixel (with the original spatial resolution of 1 km) cloud properties may affect cloud properties of the collocated AHI and AGRI pixels (with product spatial resolutions of 4 km and 5 km).…”
Section: Impact Of Cloud Inhomogeneitymentioning
confidence: 99%